2017
DOI: 10.1111/tmi.12854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of antibiotic sharing in the Philippines: antibiotic misconceptions and community‐level access to non‐medical sources of antibiotics

Abstract: Antibiotic sharing was common and was associated with misconceptions about proper antibiotic use. Antibiotics were widely available in sari-sari stands, and usually without expiration information. This study suggests that multipronged and locally tailored approaches to curbing informal antibiotic access are needed in the Philippines and similar Southeast-Asian countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 35 publications
3
78
1
4
Order By: Relevance
“…This is in the range of Beyene et al’s systemic review . Previous studies from developing countries showed that the prevalence of borrowing and lending prescription medication ranged from 35–78% and 32.7–78%, respectively, which is much higher compared with the results of our study. This is because the current study focused on recent history of borrowing or lending behaviour rather than participants’ reported history of ever borrowing or lending prescription medication, the prevalence of borrowing or lending prescription medication found in the current study is likely to be an underestimate, and the true prevalence may be higher than the prevalence identified in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in the range of Beyene et al’s systemic review . Previous studies from developing countries showed that the prevalence of borrowing and lending prescription medication ranged from 35–78% and 32.7–78%, respectively, which is much higher compared with the results of our study. This is because the current study focused on recent history of borrowing or lending behaviour rather than participants’ reported history of ever borrowing or lending prescription medication, the prevalence of borrowing or lending prescription medication found in the current study is likely to be an underestimate, and the true prevalence may be higher than the prevalence identified in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous studies, painkillers, antibiotics and allergy medicine were the most frequently borrowed and lent medicines . This is possibly because, in Saudi Arabia, allergy medications and some pain medications are easily accessible and can be obtained either with or without a prescription over the counter (OTC).…”
Section: Discussionsupporting
confidence: 82%
“…The highest negative response was found in giving one's own antibiotic to a sick family member (88.4%). This proportion is considerably higher compared to other studies done in Singapore (6.8%) and the Philippines (37%) [21,22]. This is followed by keeping leftover antibiotics to use later in case of a respiratory illness (78.9%).…”
Section: Discussionmentioning
confidence: 59%
“…Evidence has shown that the use and misuse of antibiotics may be associated with broader sociocultural [44] and sociodemographic factors [45]. In the Philippines, a study by Barber et al, found accessing unprescribed antibiotics from the local sari sari (small retail business) stand and antibiotic sharing amongst family and friends was a common practice [46]. Antibiotic prescribers are also found to be influenced by their patient's sociodemographic factors, and may adapt treatment to patient's income, antibiotic accessibility in the area and their patient's medication history [43].…”
Section: Antibiotic Use and Antibiotic Resistance In The Pork-valuechainmentioning
confidence: 99%